The practical benefit of Phadiatop test as the first-line in vitro allergen-specific immunoglobulin E (sIgE) screening of aeroallergens among Chinese asthmatics: a validation study - Zeng, Guangqiao (Ann Transl Med, 2018)
BACKGROUND: Phadiatop test is a variant of ImmunoCAP assay that covers a mixture of common aeroallergens. Its diagnostic efficiency in Chinese population remains so far inadequate. We validated Phadiatop testing with ImmunoCAP assays in a Chinese cohort. METHODS: Phadiatop test was performed for serum samples from 290 asthmatics and 92 healthy controls previously tested with “classic” ImmunoCAP for house dust mix (hx2), molds and yeasts mix (mx2), tree pollen mix (tx4) and weed mix (wx5). RESULTS: Phadiatop positivity was shown in 46.2% of 290 asthmatic patients. Using ImmunoCAP as the gold standard, the concordance rate was 91.7%; negative predictive value, 92.9%; and positive predictive value, 90.2%. The sensitivity of Phadiatop test was high for hx2 (98.2%), tx4 (100%) and wx5 (95.5%), but not for mx2 (78.4%). Yet the mx2 allergen-specific immunoglobulin E (sIgE) level in all missed cases was relatively low (0.35 to 0.90 kU(A)/L). The total Phadiatop sIgE level was correlated with the ImmunoCAP sIgE levels for all allergen mixes combined (r(s)=0.941, P<0.001) or each allergen mix, particularly the hx2 (r(s)=0.924) (all P<0.001), 0.53 kU(A)/L used as a cut-off would optimize the diagnostic performance of Phadiatop testing, yielding 89.4% sensitivity and 97.5% specificity in indentifying serums positive to any of these allergen mixes. CONCLUSIONS: Overall, Phadiatop test may efficiently detect sensitization to common aeroallergen mixes. In light of the currently rigorous administration on crude extracts for skin tests in China, using Phadiatop as the first-line test for suspected atopy can be cost-effective.